Big Soft Tissue Calcification in Posterior Ramus Mandibula Case Report: Radiograph Approach - Ilmayah, Ilmayah; Epsilawati, Lusi; Medika, Chrisna Ardhya (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2026)
Sialolithiasis is a common salivary gland disorder characterized by calcified deposits within the salivary gland or ductal system and is often detected incidentally on radiographic examination. This case study reports findings of a calcified lesion in the posterior mandible, suspected to be a salivary gland stone (sialolith). This lesion was first identified on a panoramic radiograph and subsequently evaluated with Cone Beam Computed Tomography (CBCT). A 25-year-old female presented to the radiology department with a referral for a panoramic radiographic examination, and a well-defined, irregularly circumscribed radiopaque lesion was found in the periapical area of tooth 36. CBCT was recommended, and the lesion was found to be separated from the mandibular bone. The lesion was a radiopaque lesion with a higher density than the surrounding bone, located on the left submandibular gland, with a size of ± 11.6 x 16.3 mm. Sialolith is a lesion that tends to be asymptomatic, and this case was found accidentally during a radiographic examination. This case is a large sialolith in the submandibular gland, but the patient did not notice it. Panoramic radiography and CBCT play a role in detecting sialoliths and in their optimal, complete analysis.